2019
DOI: 10.1111/cas.13890
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of carbon‐ion radiotherapy for locally advanced non‐small‐cell lung cancer

Abstract: The efficacy and safety of carbon‐ion radiotherapy (CIRT) for locally advanced non‐small‐cell lung cancer (LA‐NSCLC) remain unclear. We reported the clinical outcomes of CIRT for LA‐NSCLC. Data for 141 eligible patients who received CIRT between 1995 and 2015 were retrospectively analyzed. Local control (LC), locoregional control (LRC), progression‐free survival (PFS) and overall survival (OS) were calculated using the Kaplan‐Meier method. The median age was 75.0 years. Overall, 21 (14.9%), 57 (40.4%), 43 (30.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…The number of patients eligible for CIRT was then estimated for each disease site, based on inclusion criteria from previously published protocols and retrospective studies from Germany and Japan. The following disease sites were included: glioblastoma (based on the CLEOPATRA protocol, using CIRT as a boost [17]), hepatocellular carcinoma (PROMETHEUS-01 protocol/NCT01167374 [18]), cholangiocarcinoma (J-CROS study [19]), locally advanced pancreatic cancer (PHOENIX and CIPHER/NCT03536182 studies [9]), early and locally advanced non-small cell lung cancer (multiple retrospective studies [20][21][22][23]), localized prostate cancer (multiple retrospective studies [23][24][25][26]), soft tissue sarcomas (multiple retrospective studies [27,28]) and head and neck cancers, including salivary gland cancers (COSMIC protocol/NCT01154270 [29]), sinonasal cancers (NCT01220752 and retrospective studies [30]) and nasopharyngeal cancers (multiple retrospective studies [31,32]). Further histologic classification (such as adenoid cystic carcinoma or mucosal melanoma) of the general disease sites was possible given the limitations of the various databases used ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients eligible for CIRT was then estimated for each disease site, based on inclusion criteria from previously published protocols and retrospective studies from Germany and Japan. The following disease sites were included: glioblastoma (based on the CLEOPATRA protocol, using CIRT as a boost [17]), hepatocellular carcinoma (PROMETHEUS-01 protocol/NCT01167374 [18]), cholangiocarcinoma (J-CROS study [19]), locally advanced pancreatic cancer (PHOENIX and CIPHER/NCT03536182 studies [9]), early and locally advanced non-small cell lung cancer (multiple retrospective studies [20][21][22][23]), localized prostate cancer (multiple retrospective studies [23][24][25][26]), soft tissue sarcomas (multiple retrospective studies [27,28]) and head and neck cancers, including salivary gland cancers (COSMIC protocol/NCT01154270 [29]), sinonasal cancers (NCT01220752 and retrospective studies [30]) and nasopharyngeal cancers (multiple retrospective studies [31,32]). Further histologic classification (such as adenoid cystic carcinoma or mucosal melanoma) of the general disease sites was possible given the limitations of the various databases used ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Excellent preliminary results are reported for peripheral early stage NSCLC treated with single-fraction CIRT [8]. The efficacy and safety of CIRT for locally advanced NSCLC were recently reported by Hayashi et al [9].…”
Section: Introductionmentioning
confidence: 81%
“…in patients with LA-NSCLC [8,13]. The incidence of grade 3-4 toxicities ranged from 3.2% to 4.9%, and none of the evaluated patients experienced grade 5 toxicities.…”
Section: Introductionmentioning
confidence: 94%
“…CIRT has good dose-localizing properties [7], and thus can deliver a higher dose to the target volume than conventional photon radiotherapy while avoiding irradiation to the adjacent critical organs at risk, such as the lung, esophagus, trachea, and heart. CIRT alone can clinically achieve high local control (LC) rates with low toxicity [8][9][10][11][12][13]. Two published studies from our hospital have reported 2 year LC and overall survival (OS) rates of 83.5-93.1% and 51.9-68.0%, respectively, with CIRT alone 1 3…”
Section: Introductionmentioning
confidence: 99%